Competition among four cultivars and two selections of guava - Manica, Ivo; Kist, Henrique; Micheletto, Ênio L.; Krause, Carlos A. (Pesquisa Agropecuaria Brasileira, 1998)
Production and physical and chemical characteristics of four cultivars (IAC-4, Brune Vermelha, Riverside Vermelha and Pirassununga Vermelha) and two selections of guava (Psidium guajava L.) (RBS-1 and RBS-2) were studied in 1993 and 1994 crops, in Porto Lucena, State of Rio Grande do Sul, Brazil, in a subtropical region. The design was in randomized blocks with four replications. The production ranged from 22.05 t/ha (RBS-1 selection) to 29.96 t/ha (cv. Brune Vermelha) in 1993, and from 13.65 t/ha (RBS-2 selection) to 27.34 t/ha (cv. Pirassununga Vermelha) in 1994. RBS-1 selection showed the longest longitudinal and transversal diameters and the heaviest and thickest pulp. Cultivars and selections did not present any significant difference in regard to titratable acidity (TA), pH, total soluble solid (TSS) and TSS/TA relation. Pectin content was higher in Riverside Vermelha with 1.51% and cv. IAC-4 in vitamin C contents with 179 mg of ascorbic acid/100 g of fruit.
Keywords: Psidium guajava; physical characteristics; chemical characteristics; subtropical region